Designing minimal genomes using whole-cell models - Joshua Rees-Garbutt (Nature Portfolio, 2020)
Genome engineering will one day benefit from computational tools that can design genomes with desired functions. Here the authors develop computational design-simulate-test algorithms to design minimal genomes based on the whole-cell model of Mycoplasma genitalium.